Incisional hernia rate 3 years after midline laparotomy. Issue 2 (26th November 2013) - Fink, C; Baumann, P; Wente, M N; Knebel, P; Bruckner, T; Ulrich, A; Werner, J; Büchler, M W; Diener, M K
Abstract: Background: Incisional hernia is the most frequent long-term complication after visceral surgery, with an incidence of between 9 and 20 per cent 1 year after operation. Most controlled studies provide only short-term follow-up, and the actual incidence remains unclear. This study evaluated the incidence of incisional hernia up to 3 years after midline laparotomy in two prospective trials. Methods: Three-year follow-up data from the ISSAAC (prospective, multicentre, historically controlled) and INSECT (randomized, controlled, multicentre) trials focused on the rate of incisional hernia 1 and 3 years after surgery. Differences between the two groups were compared using t tests for continuous data and the χ 2 test for categorical data. Results: Analysis of 775 patients included in the two trials suggested that the incisional hernia rate increased significantly from 12·6 per cent at 1 year to 22·4 per cent 3 years after surgery ( P < 0.001), a relative increase of more than 60 per cent. Conclusion: This follow-up of two trials demonstrated that 1 year of clinical follow-up for detection of incisional hernia is not sufficient; follow-up for at least 3 years should be mandatory in any study evaluating the rate of postoperative incisional hernia after midline laparotomy. Abstract : Hernias often occur late